2014
DOI: 10.4103/0973-1075.125547
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers knowledge and attitude toward palliative care in an emerging tertiary centre in South-West Nigeria

Abstract: Background:Palliative care is an emerging area of medicine with potential to affect positively many chronically ill patients. This study investigated the knowledge and attitude of healthcare workers in a tertiary level hospital in Nigeria where a palliative care unit is being established.Material and Methods:The study was a cross-sectional questionnaire-based study carried out among healthcare workers in Ekiti State University Teaching Hospital, Ado-Ekiti, south-west Nigeria. The questionnaire had sections abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…This was probably due to lack of correct knowledge. This finding though is represented by few respondents' correlates well with a related study in Nigeria by Fadare, et al [7] and 2016 which showed poor knowledge of health care workers on palliative care and that 90% respondents saying palliative care is the active care of those who are dying but diverges from other study by Glare and Virik [11] whose results emphasized on early integration of palliative care approach for better patient outcomes and improved quality of life of patients and their families. Most of the respondents (58.1%) disagreed with the statement that the philosophy of IPCA is compatible with that of aggressive treatment during end of life stage.…”
Section: Discussion Of Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This was probably due to lack of correct knowledge. This finding though is represented by few respondents' correlates well with a related study in Nigeria by Fadare, et al [7] and 2016 which showed poor knowledge of health care workers on palliative care and that 90% respondents saying palliative care is the active care of those who are dying but diverges from other study by Glare and Virik [11] whose results emphasized on early integration of palliative care approach for better patient outcomes and improved quality of life of patients and their families. Most of the respondents (58.1%) disagreed with the statement that the philosophy of IPCA is compatible with that of aggressive treatment during end of life stage.…”
Section: Discussion Of Resultssupporting
confidence: 79%
“…Exactly 80.5% (66/82) respondents agreed that palliative care recognizes dying as a normal process while 84.1% (74/88) respondents were of the opinion that all dying patients would require palliative care. The use of morphine would improve the quality of life of patients according to 68.9% (42/61) of respondents [7].…”
Section: Health Workers' Knowledge On Use Of Integrated Palliative Camentioning
confidence: 99%
“…Majority of participants believed that people living with HIV/AIDS actually requires palliative care. This shows there is an understanding of the expansion of the scope of palliative from caring for cancer patients to involving HIV infection and other noncommunicable diseases[22].…”
Section: Discussionmentioning
confidence: 99%
“…There are gaps in the knowledge of PC personnel working in the field of PC and their capacities are needed to be improved by some applications [9]. Therefore, it is thought that in our country education has an important place in the integration of the new practice of PC into the health system.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies aiming to determine the perception of nurses to the PC, the themes of the definition, meaning, communication, delivering service, conditions related with the implementation, family education/ importance, collaboration, labour force, education and needs of the PC are found [9,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%